The effect of acceptance and commitment therapy on quality of life in patients with orthopedic problems - Sahar Pilevar; Saeed Teymouri; Mohammad Hossein Bayazi; Ali Reza Rajaei (Shahid Beheshti University of Medical Sciences, 2021)
Background: Bone and joint diseases have an effect on the clinical situation, high-quality of existence (QOL), and its dimensions of incapacity, causing supercharges for distinctive countries. This examine become aimed to assess the impact of acceptance and commitment therapy on QOL in orthopedic sufferers. Methods: This reading became a quasi-experimental performed as a parallel layout with pre-test and post-test. Patients stated the Promised Physiotherapy center in Mashhad decided on and had been randomly assigned to experimental (n = 12) and manipulate agencies (n = 12). The experimental organization acquired 8 weekly classes for three months, at the same time as the management organization did not receive any intervention. Statistics had been acquired by a standard QOL questionnaire and then records examine turned into finished the use of SPSS software version 25 and multivariate evaluation of covariance. Results: The average age inside the investigational agencies changed into 31.75 ± 4.71 years within the manage companies became 29.83 ± 5.27 years. Also, the common disorder timespan of the experimental organizations and manipulated businesses have been 5.64 ± 5.28 and 5.62 ± 5.81, correspondingly. The common post-test ratings of the experimental companies compared to the pre-test showed growth in subscales of QOL, however, the control agencies did no longer show such an alteration inside the post-test averages. (P-value = 0.0001) Conclusion: the use of acceptance and commitment remedy as an effective and complementary psychological intervention in enhancing the QOL in orthopedic sufferers is usually recommended.